2017
DOI: 10.7554/elife.28023
|View full text |Cite
|
Sign up to set email alerts
|

Cell differentiation defines acute and chronic infection cell types in Staphylococcus aureus

Abstract: A central question to biology is how pathogenic bacteria initiate acute or chronic infections. Here we describe a genetic program for cell-fate decision in the opportunistic human pathogen Staphylococcus aureus, which generates the phenotypic bifurcation of the cells into two genetically identical but different cell types during the course of an infection. Whereas one cell type promotes the formation of biofilms that contribute to chronic infections, the second type is planktonic and produces the toxins that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
55
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 135 publications
(203 reference statements)
4
55
0
Order By: Relevance
“…This secreted enzyme was shown to mediate the degradation of the extracellular DNA (eDNA) matrix of biofilm, resulting in the detachment of cells during the early stages of biofilm development and allowing microcolony formation. In contrast to the previous dogma, which was based on the presumption that all S. aureus cells within a population are similar with respect to virulence gene expression, our current results support a growing awareness that expression of some virulence genes is limited to a subpopulation of cells under (33,34). We also demonstrated that the stochastic expression of these genes is likely to be mediated by the well-known SaePQRS regulatory system.…”
Section: Discussionsupporting
confidence: 60%
“…This secreted enzyme was shown to mediate the degradation of the extracellular DNA (eDNA) matrix of biofilm, resulting in the detachment of cells during the early stages of biofilm development and allowing microcolony formation. In contrast to the previous dogma, which was based on the presumption that all S. aureus cells within a population are similar with respect to virulence gene expression, our current results support a growing awareness that expression of some virulence genes is limited to a subpopulation of cells under (33,34). We also demonstrated that the stochastic expression of these genes is likely to be mediated by the well-known SaePQRS regulatory system.…”
Section: Discussionsupporting
confidence: 60%
“…These abilities are likely to contribute to the persistence of S. aureus in airways of patients with chronic lung diseases despite appropriate antimicrobial treatments [18, 19]. S. aureus persistence is associated with a drastic decrease in metabolism [20], a decrease in the expression of virulence factors and an increase in the expression of bacterial adhesins [21]. Such profile is typical of small-colony variants (SCVs) that are defined by small-sized colonies [15, 22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus persistence is linked to a drastic decrease in metabolism (such as a reduction in the Krebs cycle activity) [27] and is generally associated with a decrease in the expression of virulence factors and an increase in the expression of bacterial adhesins [28]. Such profile is typical of small-colony variants (SCVs) that are defined by their slow growth rate resulting in small-sized colonies [22, 29, 30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clusters essentially act like plasmid reservoirs and generate non-linear dynamics around overall plasmid copy number, which favours robustness. In addition, these clusters add a different viewpoint to the analysis of bacterial differentiation within a population [26] - often a knowledge gap - which is advantageous to us.…”
Section: Resultsmentioning
confidence: 99%